2018
DOI: 10.21037/jtd.2018.07.88
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of postoperative analgesia after thoracotomy—a randomized controlled trial

Abstract: TEA provided superior anaesthesia compared to PCA in our study group. Use of PCA oxycodone in postoperative pain management after open thoracotomy provides similar nociception control compared to morphine but is associated with less sedation and patients using oxycodone IVPCA require smaller doses of rescue analgesia compared to systemic morphine IVPCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
(58 reference statements)
0
26
1
Order By: Relevance
“…It has previously been reported that poorly controlled acute postoperative pain is a risk factor associated with respiratory complications [27], and that postoperative pain may lead to the development of atelectasis because it can interfere with the normal activity of respiratory muscles and forced respiratory effort [28]. On the other hand, other studies have shown that epidural analgesia provides better postoperative pain control than systemic opioid administration in abdominal or open thoracotomy surgery [29,30]. In the present study, epidural patient-controlled analgesia was used less commonly in patients reversed with sugammadex than those reversed with pyridostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that poorly controlled acute postoperative pain is a risk factor associated with respiratory complications [27], and that postoperative pain may lead to the development of atelectasis because it can interfere with the normal activity of respiratory muscles and forced respiratory effort [28]. On the other hand, other studies have shown that epidural analgesia provides better postoperative pain control than systemic opioid administration in abdominal or open thoracotomy surgery [29,30]. In the present study, epidural patient-controlled analgesia was used less commonly in patients reversed with sugammadex than those reversed with pyridostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…In thoracic surgery, intravenous patient controlled analgesia (PCA), thoracic epidural and continuous paravertebral block are strictly recommended by international guidelines. [45] However, these regional techniques are invasive, riskful,[6] requiring skilled operators and a challenging postoperative management. Moreover, continuous regional techniques may be at risk of failure, due to catheter displacement or infusion pump malfunction.…”
Section: Introductionmentioning
confidence: 99%
“…25 Although conflicting results existed in the literature, TEA proved its efficacy over conventional analgesia and other regional techniques. [1][2][3][6][7][8][9]26,27 Reducing the requirement for rescue analgesics, sustained mode of action and relatively low incidence of serious procedurerelated complications are the main advantages of TEA, which made it accepted as the gold standard method. 1,6,9 Along with these, TEA has superiority over conventional analgesia through preserving cardiopulmonary functions, diminishing stress response, facilitating the recovery of gastrointestinal motility and improving immune function.…”
Section: Discussionmentioning
confidence: 99%